Application of amino acid-based assembly, reagent of amino acid-based assembly, cosmetic composition and preparation method and application of cosmetic composition

By using amino acid-based assemblies and anionic polysaccharide polymers in cosmetics of blue copper peptides, a stable anionic solution system was constructed, which solved the problem of instability of blue copper peptides, and achieved its stable application and anti-aging repair effect in cosmetics.

CN119606781APending Publication Date: 2025-03-14CHANGZHOU SMART BIOTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702864.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The instability of blue copper peptides leads to limited application in the cosmetics field, especially under the influence of light, heat, pH and ion exchange factors, which are prone to inactivation, discoloration and fading.

Method used

By using amino acid-based assemblies, such as arginine malate and glycyrrhizine arginine, combined with anionic polysaccharide polymers, a stable anionic solution system is constructed to protect copper ions and weaken the competition among copper ions, thereby enhancing the stability of blue copper peptides.

Benefits of technology

It effectively improves the light stability and thermal stability of blue copper peptide, solves the problem of difficulty in application in the field of cosmetics technology, and realizes stable application in repair and anti-aging skin care products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153785700000131
    Figure BDA0005153785700000131
  • Figure BDA0005153785700000132
    Figure BDA0005153785700000132
  • Figure BDA0005153785700000141
    Figure BDA0005153785700000141
Patent Text Reader

Abstract

The invention discloses application of an amino acid-based assembly, a reagent of the amino acid-based assembly, a cosmetic composition and a preparation method and application of the cosmetic composition, and relates to the field of cosmetics. The invention provides application of an amino acid-based assembly in preparation of a reagent for improving stability of blue copper peptide. The amino acid-based assembly comprises arginine malate and / or arginine glycyrrhizinate. The amino acid-based assemblies such as arginine malate and glycyrrhizic acid arginine salt can buffer the blue copper peptide in the system and weaken copper ion competition, the stability of the blue copper peptide can be effectively improved, and the problem that the blue copper peptide is difficult to apply in the technical field of cosmetics is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of cosmetics, and in particular to the application of an amino acid-based assembly and reagents thereof, a cosmetic composition and a preparation method and application thereof. Background Art

[0002] GHK, short for tripeptide-1, has an amino acid sequence of glycyl-L-histidyl-L-lysine and a molecular formula of C 14 H 24 N 6 O 4 , CAS number is 49557-75-7, its stable pH range is 3.0-6.0, as a signal short peptide, it can repair the skin and promote collagen production. GHK has a strong affinity with copper ions and easily forms a complex GHK-Cu (blue copper peptide), whose standard Chinese name is tripeptide-1 copper. Blue copper peptide has good soothing, repairing, anti-aging, anti-wrinkle, anti-sugar, and wound healing effects. The coordination bond between GHK and copper ions in the blue copper peptide structure is unstable and is easily affected by factors such as light, heat, oxygen, pH, ion properties, and ion exchange, causing inactivation, fading, and discoloration. The instability of blue copper peptides is mainly caused by unstable factors caused by light, heat, pH, and ion exchange. For example, under acidic conditions of pH <3.0, the copper ions of blue copper peptides are in a non-ionized form and their solution is light blue. Under alkaline conditions of pH>7.5, the color of the blue copper peptide solution is the most beautiful blue-purple. Alkaline conditions cause the affinity of GHK to copper ions to decrease, affecting the structural stability of GHK-Cu. The blue copper peptide solution is easily affected by the ionic properties of the system. If it is combined with cationic substances, ion exchange is likely to occur. For example, when the blue copper peptide is combined with the cationic polysaccharide polymer chitosan, the amino and hydroxyl groups of its molecular chain can enhance the affinity of chitosan to copper ions through cross-linking, compete for copper ions, and easily generate chitosan-copper, thereby inactivating the blue copper peptide.

[0003] Therefore, due to the instability of blue copper peptides, the application of blue copper peptides in the cosmetics field is limited. Summary of the invention

[0004] Based on the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide the application of amino acid-based assemblies and reagents thereof, cosmetic compositions and preparation methods and applications thereof, aiming to solve the problem of poor stability of blue copper peptides.

[0005] The technical solution of the present invention is as follows:

[0006] In a first aspect of the present invention, there is provided an application of an amino acid-based assembly in the preparation of a reagent for improving the stability of a blue copper peptide, wherein the amino acid-based assembly comprises arginine malate and / or glycyrrhizic acid arginine salt.

[0007] In a second aspect of the present invention, a reagent for improving the stability of blue copper peptide is provided, wherein the reagent for improving the stability of blue copper peptide comprises an amino acid-based assembly and an anionic polysaccharide polymer, and the amino acid-based assembly comprises arginine malate and / or glycyrrhizic acid arginine salt.

[0008] Optionally, the anionic polysaccharide polymer includes at least one of xanthan gum, sodium hyaluronate, gellan gum and sphingosine gum.

[0009] Optionally, the reagent for improving the stability of blue copper peptide further comprises polyol, β-glucan, glycerol glucoside, preservative and antibacterial agent and deionized water;

[0010] Alternatively, the reagent for improving the stability of blue copper peptide further comprises polyol, β-glucan, glycerol glucoside mixture, preservative and antibacterial agent and deionized water, and the glycerol glucoside mixture consists of glycerol glucoside, 1,2-pentanediol and water.

[0011] Optionally, the reagent for improving the stability of blue copper peptide includes the following components by mass:

[0012] 0.1-30 parts of polyol, 0.01-0.5 parts of amino acid-based assembly, 0.01-2 parts of anionic polysaccharide polymer, 0.01-5 parts of β-glucan, 0.01-4 parts of glycerol glucoside, 0.1-10 parts of preservative and antibacterial agent, and 43.5-99.75 parts of water;

[0013] Or, by weight, the reagent for improving the stability of blue copper peptide includes the following components:

[0014] 0.1-30 parts of polyol, 0.01-0.5 parts of amino acid-based assembly, 0.01-2 parts of anionic polysaccharide polymer, 0.01-5 parts of β-glucan, 0.01-4 parts of glycerol glucoside mixture, 0.1-10 parts of preservative and antibacterial agent, and 43.5-99.75 parts of water;

[0015] The glycerol glucoside mixture is composed of the following components in percentage by mass:

[0016] Glyceryl glucoside 65%, 1,2-pentanediol 5% and water 30%.

[0017] Optionally, the polyol includes at least one of glycerol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, methyl propanediol and dipropylene glycol;

[0018] The antiseptic and antibacterial agent includes at least one of 1,2-pentanediol, 1,2-hexanediol, p-hydroxyacetophenone, chlorphenesin, ethylhexylglycerin and methylparaben.

[0019] The third aspect of the present invention provides a cosmetic composition, wherein the cosmetic composition comprises the reagent for improving the stability of the blue copper peptide as described above and the blue copper peptide.

[0020] Optionally, the cosmetic composition comprises the following components by mass percentage:

[0021] Blue copper peptide 0.01%-5%, polyol 0.1%-30%, amino acid-based assembly 0.01%-0.5%, anionic polysaccharide polymer 0.01%-2%, β-glucan 0.01%-5%, glycerol glucoside 0.01%-4%, preservative and antibacterial agent 0.1%-10% and the balance to 100% water;

[0022] Or, measured by mass percentage, the cosmetic composition comprises the following components:

[0023] Blue copper peptide 0.01%-5%, polyol 0.1%-30%, amino acid-based assembly 0.01%-0.5%, anionic polysaccharide polymer 0.01%-2%, β-glucan 0.01%-5%, glycerol glucoside mixture 0.01%-4%, preservative and antibacterial agent 0.1%-10% and the balance to 100% water;

[0024] The glycerol glucoside mixture is composed of the following components in percentage by mass:

[0025] Glyceryl glucoside 65%, 1,2-pentanediol 5% and water 30%.

[0026] The fourth aspect of the present invention provides a method for preparing the cosmetic composition of the present invention as described above, wherein, by weight percentage, the method comprises the following steps:

[0027] Mix 0.01%-5% of blue copper peptide with 20% of water, then add 0.01%-0.5% of amino acid-based assembly, and mix to obtain a first mixed solution;

[0028] 0.01%-2% of anionic polysaccharide polymer, 0.1%-30% of polyol and the balance of 100% of water are added into a vacuum emulsifying pot, heated to 80-85°C with stirring, kept warm in a water bath for 30 minutes, cooled to 70-75°C, 0.1%-10% of preservative and antibacterial agent is added, stirred and dissolved, and then cooled to 30-35°C, 0.01%-5% of β-glucan, glycerol glucoside mixture or 0.01%-4% of glycerol glucoside and the first mixed solution are added, and mixed to obtain the cosmetic composition.

[0029] The fifth aspect of the present invention provides the use of the cosmetic composition as described above and / or the cosmetic composition prepared by the preparation method as described above in the preparation of repair and anti-aging skin care products.

[0030] Beneficial effects: The amino acid-based assemblies such as arginine malate and glycyrrhizic acid arginine salt in the present invention can provide a stable ion environment for the blue copper peptide molecular structure in the solution system, can buffer the blue copper peptide in the system and weaken the competition for copper ions, can effectively improve the stability of the blue copper peptide, and solve the problem of the difficulty in applying the blue copper peptide in the field of cosmetic technology. DETAILED DESCRIPTION

[0031] The present invention provides the application of amino acid-based assemblies and reagents thereof, cosmetic compositions and preparation methods and applications thereof. To make the purpose, technical solutions and effects of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0032] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0033] In view of the fact that blue copper peptides in the prior art are prone to inactivation, discoloration, fading, etc. during use, an embodiment of the present invention provides the use of an amino acid-based assembly in the preparation of a reagent for improving the stability of blue copper peptides, wherein the amino acid-based assembly includes arginine malate and / or glycyrrhizic acid arginine salt.

[0034] Blue copper peptide needs a stable ionic environment in the solution system, and amino acid-based assemblies such as arginine malate and glycyrrhizic acid arginine salt can provide a stable ionic environment for the molecular structure of blue copper peptide in the solution system. At the same time, arginine malate and glycyrrhizic acid arginine salt are consistent with the properties of GHK in the solution system, and are anionic in nature. There is a synergistic effect, which can be compatible with copper ions, and then can protect copper ions, avoiding competition of other groups for copper ions and causing copper ions to fail. In addition, the amino acid-based assembly also has an effect on the acidity and alkalinity of the system, and can stabilize the pH value of the entire system. Therefore, the amino acid-based assembly can provide a stable anionic solution system, so that the copper ions in the blue copper peptide coexist in the anionic solution environment, and the protection of copper ions is achieved, thereby improving the stability of the blue copper peptide. The amino acid-based assembly provided by the present invention plays a buffering role and weakens the competition of copper ions on the blue copper peptide in the system, which can effectively improve the stability of the blue copper peptide and solve the problem of the difficulty of applying the blue copper peptide in the field of cosmetic technology.

[0035] The embodiment of the present invention also provides a reagent for improving the stability of blue copper peptide, wherein the reagent for improving the stability of blue copper peptide comprises an amino acid-based assembly and an anionic polysaccharide polymer, wherein the amino acid-based assembly comprises arginine malate and / or glycyrrhizic acid arginine salt.

[0036] In the present invention, anionic polysaccharide polymers can cooperate with amino acid-based assemblies to weaken ion exchange in a suitable pH range (6.0-7.0), and anionic polysaccharide polymers and copper ions can coexist under the pH environment to play a synergistic effect. Specifically, anionic polysaccharide polymers play a role in balancing charges, GHK in blue copper peptides is negatively charged, and copper ions are positively charged, and the D-glucuronic acid on the structure of anionic polysaccharide polymers contains COOH, which is negatively charged after hydrolysis, and the charge performance of negatively charged anionic polysaccharide polymers is the same as that of GHK, so anionic polysaccharide polymers play a synergistic protective role in the system. In addition, anionic polysaccharide polymers have acid resistance, ion resistance, and anti-enzymatic effects in the solution system, and have good light stability and heat stability, therefore, while anionic polysaccharide polymers play their own light stability and heat stability, because of good compatibility with copper ions, blue copper peptides in the system are also improved. Light stability and heat stability. Therefore, the amino acid-based assemblies in the system can protect copper ions and reduce the competition for copper ions. On the one hand, the anionic polysaccharide polymer works synergistically with the amino acid-based assemblies to protect copper ions and reduce the competition for copper ions. On the other hand, it uses its own heat and light stability to improve the stability of copper ions in the system and improve the photostability and thermal stability of the blue copper peptide.

[0037] In addition, anionic polysaccharide polymers themselves are thickeners and have moisturizing effects, providing a certain skin feel when used in cosmetics.

[0038] In some embodiments, arginine malate is derived from arginine and malic acid, and is an amino acid-based assembly prepared by supramolecular technology with a molar ratio of arginine and malic acid (i.e., the molar ratio of arginine and malic acid salt is 2:1), with a CAS number of 41989-03-1 and an EINECS accession number of 255-608-0. Among them, malic acid is a proton donor and arginine is a proton acceptor.

[0039] Glycyrrhizic acid arginine salt is derived from glycyrrhizic acid and arginine, specifically an amino acid-based assembly prepared by supramolecular technology with a molar ratio of glycyrrhizic acid and arginine of 1:2 (i.e., the molar ratio of glycyrrhizic acid and arginine salt is 1:2). Glycyrrhizic acid arginine salt can be purchased. Glycyrrhizic acid is a proton donor and arginine is a proton acceptor. Glycyrrhizic acid arginine salt has a soothing and repairing effect when applied externally to the skin.

[0040] In some embodiments, the anionic polysaccharide polymer includes at least one of xanthan gum, sodium hyaluronate, gellan gum and sphingosine gum, but is not limited thereto. The anionic polysaccharide polymer has the functions of thickening, moisturizing, product sensory modification and synergistic protection of blue copper peptide.

[0041] Xanthan gum is a polymer of a pentasaccharide repeating unit structure consisting of D-glucose, D-mannose, D-glucuronic acid, acetic acid and pyruvic acid. The D-glucuronic acid in the xanthan gum structure contains a carboxyl group (-COOH), which is anionic, has a low charge density, and is highly resistant to acid, alkali, salt, and heat.

[0042] Sodium hyaluronate is a linear anionic polysaccharide polymer composed of disaccharide repeating units composed of D-glucuronic acid and N-acetylglucosamine. The D-glucuronic acid in its structure contains a carboxyl group (-COOH) and exhibits anionic properties. In some embodiments, the molecular weight of the sodium hyaluronate ranges from 200,000 to 2,000,000.

[0043] Gellan gum is a polymer with a tetrasaccharide repeating unit structure consisting of D-glucose, D-glucuronic acid, D-glucose, and L-rhamnose. The D-glucuronic acid in the gellan gum structure contains a carboxyl group (-COOH) and exhibits anionic properties.

[0044] The standard Chinese name of sphingomyelin is the extract of fermentation products of Sphingomonas (SPHINGOMONAS). Sphingomyelin is a polymer of hexasaccharide repeating unit structure composed of 4 linear glycones as the main chain and 2 glycones as the side chain. The D-glucuronic acid in the structure of sphingomyelin contains a carboxyl group (-COOH) and exhibits anionic properties. Sphingomyelin has low charge density and is resistant to acid, alkali, salt, heat, etc.

[0045] In some embodiments, when the amino acid-based assembly includes arginine malate and glycyrrhizic acid arginine salt, the mass ratio of arginine malate to glycyrrhizic acid arginine salt is 1:(1-2), for example, it can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or 1:2, etc.

[0046] In some embodiments, the reagent for improving the stability of the blue copper peptide includes an amino acid-based assembly (including arginine malate and / or glycyrrhizic acid arginine salt), an anionic polysaccharide polymer, a polyol, β-glucan, glycerol glucoside, a preservative and an antibacterial agent, and deionized water. In some specific embodiments, the reagent for improving the stability of the blue copper peptide includes the following components by weight:

[0047] 0.1-30 parts of polyol, 0.01-0.5 parts of amino acid-based assembly, 0.01-2 parts of anionic polysaccharide polymer, 0.01-5 parts of beta-glucan, 0.01-4 parts of glycerol glucoside, 0.1-10 parts of preservative and antibacterial agent and 43.5-99.75 parts of deionized water.

[0048] In some embodiments, the reagent for improving the stability of blue copper peptide includes an amino acid-based assembly (including arginine malate and / or glycyrrhizic acid arginine salt), an anionic polysaccharide polymer, a polyol, β-glucan, a glycerol glucoside mixture, a preservative and an antibacterial agent, and deionized water, wherein the glycerol glucoside mixture is composed of glycerol glucoside, 1,2-pentanediol, and water.

[0049] In some specific embodiments, the reagent for improving the stability of blue copper peptide includes the following components by weight:

[0050] 0.1-30 parts of polyol, 0.01-0.5 parts of amino acid-based assembly, 0.01-2 parts of anionic polysaccharide polymer, 0.01-5 parts of β-glucan, 0.01-4 parts of glycerol glucoside mixture, 0.1-10 parts of preservative and antibacterial agent, and 43.5-99.75 parts of deionized water;

[0051] The glycerol glucoside mixture is composed of the following components in percentage by mass:

[0052] Glyceryl glucoside 65%, 1,2-pentanediol 5% and water 30%.

[0053] The amino acid-based assembly plays a role in weakening the competition of copper ions by constructing an anionic solution system. The D-glucuronic acid on the structure of the anionic polysaccharide polymer contains a carboxyl group (-COOH), and its solution system also presents anionic properties, which are compatible with copper ions, similar to the properties of GHK in nature. Specifically, the charge of the anionic polysaccharide polymer in the solution is negative, the charge of the copper ion is positive, and GHK and the amino acid-based assembly are also negative, so the anionic polysaccharide polymer coexists in the system. Anionic polysaccharide polymers, such as sodium hyaluronate, gellan gum, sphingosine gum, xanthan gum, etc., have acid resistance, ion resistance, anti-enzyme effects, and good light stability and heat stability in the solution system. Therefore, while the anionic polysaccharide polymer exerts its own light stability and heat stability, because of its good compatibility with copper ions, it also improves the light stability and heat stability of the blue copper peptide in the system. Therefore, the amino acid-based assembly synergizes with the anionic polysaccharide polymer to protect copper ions, weaken the competition of copper ions, and improve the heat resistance and light stability of the blue copper peptide. In addition, the reagent system provided above can not only achieve relevant efficacy, but also play a role in stabilizing the blue copper peptide.

[0054] Among them, the polyol includes but is not limited to at least one of glycerol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, methyl propanediol and dipropylene glycol, which acts as a humectant to aid solubility, moisturize and modify the sensory properties of the product.

[0055] β-Glucan is a natural product, a polysaccharide composed of glucose molecules connected by β-1,3-bonds and β-1,6-bonds. It exists in many plants and fungi, such as mushrooms, yeast, algae, etc. β-Glucan has many important biological activities and pharmacological effects, and is widely used in medicine, health care products, food and other fields. β-1,3-bonds have a repairing function, and β-1,6-bonds have a moisturizing function. Adding β-Glucan can enhance the repairing and moisturizing effects of the reagent, and when used in the preparation of cosmetics, it can enhance its repairing and moisturizing effects.

[0056] Glyceryl glucoside, referred to as GG, is composed of one glucose molecule and one glycerol molecule connected by a glycosidic bond, and its glycosidic bond can be established between the C1 hydroxyl group of glucose and any hydroxyl group of glycerol. Glyceryl glucoside has the functions of moisturizing the skin, promoting collagen synthesis in dermal cells, and increasing the metabolic rate of aging cells. Adding glyceryl glucoside to the reagent can enhance the moisturizing and repairing effect of the reagent.

[0057] The antiseptic and antibacterial agent includes but is not limited to at least one of 1,2-pentanediol, 1,2-hexanediol, p-hydroxyacetophenone, chlorphenesin, ethylhexylglycerin and methylparaben, which mainly plays an antiseptic and antibacterial role.

[0058] An embodiment of the present invention further provides a cosmetic composition, wherein the cosmetic composition comprises the reagent for improving the stability of the blue copper peptide as described above in the embodiment of the present invention and the blue copper peptide.

[0059] The cosmetic composition provided by the present invention has good light stability and thermal stability, can give full play to the effect of blue copper peptide, has anti-aging effect, and solves the problem that blue copper peptide is difficult to apply in the field of cosmetic technology.

[0060] In some embodiments, the cosmetic composition includes the following components by weight percentage:

[0061] Blue copper peptide 0.01%-5%, polyol 0.1%-30%, amino acid-based assembly 0.01%-0.5%, anionic polysaccharide polymer 0.01%-2%, β-glucan 0.01%-5%, glycerol glucoside 0.01%-4%, preservative and antibacterial agent 0.1%-10% and the balance to 100% is deionized water.

[0062] In some embodiments, the cosmetic composition includes the following components by weight percentage:

[0063] Blue copper peptide 0.01%-5%, polyol 0.1%-30%, amino acid-based assembly 0.01%-0.5%, anionic polysaccharide polymer 0.01%-2%, β-glucan 0.01%-5%, glycerol glucoside mixture 0.01%-4%, preservative and antibacterial agent 0.1%-10% and deionized water as the balance to 100%;

[0064] The glycerol glucoside mixture is composed of the following components in percentage by mass:

[0065] Glyceryl glucoside 65%, 1,2-pentanediol 5% and water 30%.

[0066] The pH range of the above-mentioned cosmetic composition is 6.0-7.0. The amino acid-based assembly cooperates with the anionic polysaccharide polymer to construct a solution environment where ions coexist by protecting the affinity of the GHK structure to copper ions, so that the amino acid-based assembly, the anionic polysaccharide polymer and the blue copper peptide coexist in the solution, while effectively improving the photostability and thermal stability of the blue copper peptide.

[0067] The present invention also provides a method for preparing the cosmetic composition as described above in the present invention, wherein the method comprises the following steps, calculated by weight percentage:

[0068] Mix 0.01%-5% of blue copper peptide with 20% of water, then add 0.01%-0.5% of amino acid-based assembly, and mix to obtain a first mixed solution;

[0069] 0.01%-2% of anionic polysaccharide polymer, 0.1%-30% of polyol and the balance of 100% of water are added into a vacuum emulsifying pot, heated to 80-85°C with stirring, kept warm in a water bath for 30 minutes, cooled to 70-75°C, 0.1%-10% of preservative and antibacterial agent is added, stirred and dissolved, and then cooled to 30-35°C, 0.01%-5% of β-glucan, glycerol glucoside mixture or 0.01%-4% of glycerol glucoside and the first mixed solution are added, and mixed to obtain the cosmetic composition.

[0070] The present invention also provides a use of the cosmetic composition described above in the present invention and / or the cosmetic composition prepared by the preparation method described above in the present invention in the preparation of repair and anti-aging skin care products.

[0071] In some embodiments, the anti-aging skin care products include repairing and anti-aging lotions (such as repairing and anti-aging toners), repairing and anti-aging essences, or repairing and anti-aging facial masks, etc.

[0072] The present invention will be further described below by means of specific examples.

[0073] In the following examples, unless otherwise specified, the raw materials used are commercially available products. For example, arginine glycyrrhizinate was purchased from Guangdong Xuanjia Medical Health Technology Co., Ltd. under the trade name Xuanfuxiu.

[0074] The glycerol glucoside mixtures used in the following examples and comparative examples are composed of the following components in percentage by mass:

[0075] Glyceryl glucoside 65%, 1,2-pentanediol 5% and water 30%.

[0076] Example 1

[0077] This embodiment provides a cosmetic composition, which comprises the following components by weight percentage:

[0078] Deionized water 91.38%, 1,3-propylene glycol 3%, 1,3-butylene glycol 3%, xanthan gum 0.35%, sodium hyaluronate 0.05%, arginine malate 0.05%, glycyrrhizic acid arginine salt 0.05%, blue copper peptide 0.1%, β-glucan 0.02%, glycerol glucoside mixture 1%, p-hydroxyacetophenone 0.5% and 1,2-hexanediol 0.5%.

[0079] This embodiment also provides a method for preparing the above cosmetic composition, which comprises the following steps, calculated by weight percentage:

[0080] Mix 0.1% of blue copper peptide and 20% of deionized water to dissolve, add 0.05% of arginine malate and 0.05% of glycyrrhizic acid arginine salt, stir and dissolve to obtain a first mixed solution, and seal for standby use;

[0081] Mix and disperse 0.35% xanthan gum, 0.05% sodium hyaluronate, 3% 1,3-propylene glycol, and 3% 1,3-butylene glycol, add 71.38% deionized water, and then place in a vacuum emulsifying pot, stir and heat to 85°C, keep warm in a water bath for 30 minutes, and cool down;

[0082] When the temperature drops to 75°C, add 0.5% p-hydroxyacetophenone and 0.5% 1,2-hexanediol, stir to dissolve, and continue to cool;

[0083] When the temperature drops to 30° C., 0.02% of β-glucan, 1% of the glycerol glucoside mixture and the first mixed solution are added, stirred, dispersed and dissolved to obtain the cosmetic composition.

[0084] The cosmetic composition can be used for refreshing repairing and anti-aging facial mask liquid or essence liquid products.

[0085] Example 2

[0086] This embodiment provides a cosmetic composition, which comprises the following components by weight percentage:

[0087] Deionized water 91.88%, glycerol 3%, 1,3-butanediol 3%, sphingosine gum 0.5%, arginine malate 0.03%, glycyrrhizinate arginine salt 0.04%, blue copper peptide 0.2%, β-glucan 0.05%, glycerol glucoside mixture 0.5%, p-hydroxyacetophenone 0.2%, 1,2-hexanediol 0.5% and chlorphenesin 0.1%.

[0088] The preparation method of the cosmetic composition is shown in Example 1.

[0089] The cosmetic composition can be used for moisturizing, repairing and anti-aging essence products.

[0090] Example 3

[0091] This embodiment provides a cosmetic composition, which comprises the following components by weight percentage:

[0092] Deionized water 90.1%, glycerol 4%, dipropylene glycol 3%, gellan gum 0.1%, arginine malate 0.04%, glycyrrhizic acid arginine salt 0.06%, blue copper peptide 0.1%, β-glucan 0.1%, glyceryl glucoside mixture 1.5%, p-hydroxyacetophenone 0.45%, 1,2-hexanediol 0.5% and ethylhexylglycerol 0.05%.

[0093] The preparation method of the cosmetic composition is shown in Example 1.

[0094] The cosmetic composition can be used for refreshing repairing and anti-aging toner or skin care water products.

[0095] Example 4

[0096] This embodiment provides a cosmetic composition, which comprises the following components by weight percentage:

[0097] Deionized water 90.17%, 1,3-butylene glycol 5%, sodium hyaluronate 0.1%, sphingosine gum 0.4%, arginine malate 0.1%, glycyrrhizinate arginine salt 0.13%, blue copper peptide 0.3%, β-glucan 0.05%, glycerol glucoside mixture 3%, chlorphenesin 0.15% and 1,2-hexanediol 0.6%.

[0098] The preparation method of the cosmetic composition is shown in Example 1.

[0099] The cosmetic composition can be used for a soft and moisturizing repairing and anti-aging essence or a facial mask liquid product.

[0100] Example 5

[0101] This embodiment provides a cosmetic composition, which comprises the following components by weight percentage:

[0102] Deionized water 88.55%, 2,3-butanediol 6%, xanthan gum 0.5%, arginine malate 0.02%, glycyrrhizic acid arginine salt 0.03%, blue copper peptide 0.2%, β-glucan 0.2%, glycerol glucoside mixture 2%, 1,2-pentanediol 2% and p-hydroxyacetophenone 0.5%.

[0103] The preparation method of the cosmetic composition is shown in Example 1.

[0104] The cosmetic composition can be used for repairing anti-aging essence or facial mask products.

[0105] Comparative Example 1

[0106] This comparative example provides a cosmetic composition (without adding an amino acid-based assembly), which comprises the following components by weight percentage:

[0107] Deionized water 90.78%, 1,3-propylene glycol 3%, 1,3-butylene glycol 4%, sodium hyaluronate 0.35%, xanthan gum 0.05%, blue copper peptide 0.3%, β-glucan 0.02%, glycerol glucoside mixture 0.5%, 1,2-hexanediol 0.5% and p-hydroxyacetophenone 0.5%.

[0108] The preparation method of the cosmetic composition is shown in Example 1.

[0109] Comparative Example 2

[0110] This comparative example provides a cosmetic composition (anionic polysaccharide is replaced by hydroxyethyl cellulose), which comprises the following components by mass percentage:

[0111] Deionized water 90.21%, 1,3-propylene glycol 3%, 1,3-butylene glycol 4%, hydroxyethyl cellulose 0.4%, arginine malate 0.03%, arginine oxalate 0.04%, blue copper peptide 0.3%, β-glucan 0.02%, glycerol glucoside mixture 1%, 1,2-hexanediol 0.5% and p-hydroxyacetophenone 0.5%.

[0112] The preparation method of the cosmetic composition is shown in Example 1.

[0113] The cosmetic compositions in Examples 1 to 5 and Comparative Examples 1 to 2 were sampled and tested for pH, light stability and thermal stability, and the retention rate of the blue copper peptide under light and heat treatment conditions was detected. In the light stability test and the thermal stability test, the stability of the blue copper peptide can be investigated by changes in appearance. Copper ion compounds are color-developing substances. The instability of the blue copper peptide is generally accompanied by changes in the color of the appearance. The stability of the blue copper peptide in the composition system can be preliminarily judged based on the changes in the appearance color of the test sample. Lightening, darkening, fading, and greening are all manifestations of the instability of the blue copper peptide. It is further determined that the stability of the blue copper peptide can be accurately described by the retention rate, and the content of the blue copper peptide in the composition is quantitatively detected by HPLC (high performance liquid chromatography) to determine the stability under different conditions. The test results of the cosmetic compositions in Examples 1-5 and Comparative Examples 1-2 are compared and analyzed, as follows:

[0114] (1) Thermal stability test

[0115] 20 grams of the cosmetic compositions in the above Examples 1-5 and Comparative Examples 1-2 were sampled with a test glass bottle and placed in a constant temperature and humidity chamber at 45°C ± 2°C for 90 days, and the color changes were recorded on days 0, 30, 60, and 90 (day 0 was before the test). 1 g of the sample was taken at each time point for HPLC detection of the blue copper peptide content, and the blue copper peptide content on day 0 was used as a comparison to calculate the retention rate of the blue copper peptide in the cosmetic composition. The cosmetic compositions in each example and comparative example were placed in a room temperature environment of 25°C ± 2°C as a blank control group.

[0116] in,

[0117] i: number of samplings; n: total number of samples taken in this experiment (i.e. n is 4); Ci: concentration of blue copper peptide at the i-th sampling (mg / g); Mr is the sampling volume for each sampling (Mr=1g); M0 is the total sample volume (M0=20g); C1: concentration of blue copper peptide at the first sampling (i.e. sampling on day 0) (mg / g).

[0118] The color change results and the blue copper peptide retention rate results are shown in Table 1 and Table 2, respectively.

[0119] Table 1. Color change results of thermal stability test

[0120]

[0121] From the above results, it can be seen that the cosmetic compositions in Examples 1-5 have good heat resistance in the 90-day thermal stability test, without obvious discoloration and fading, and the stability at room temperature is also very good. The cosmetic composition in Comparative Example 1 darkened in color on the 30th day, and was obviously unstable. The cosmetic composition in Comparative Example 2 began to lighten in color from the 60th day. In the room temperature control group, the composition in Comparative Example 1 began to darken in color on the 60th day, and the stability under room temperature conditions was also poor.

[0122] Table 2. Thermal stability test blue copper peptide retention rate

[0123]

[0124] From the above results, it can be seen that the cosmetic compositions in Examples 1-5 have good stability, and the retention rates in the 90-day blue copper peptide thermal stability test are all above 98%, which is basically consistent with the retention rate of the room temperature control group. However, the color of Comparative Example 1 darkened on the 30th day, and the blue copper peptide retention rate was 73.2%, and the room temperature control group also showed a decrease in retention rate on the 60th day, with a retention rate of 74.3% on the 60th day. The color of Comparative Example 2 became significantly lighter on the 60th day, and the blue copper peptide retention rate was 85.6%. The retention rate of the room temperature control group was still around 90% for 90 days. The thermal stability of the cosmetic compositions in Examples 1-5 is significantly better than that of Comparative Examples 1-2, and Comparative Example 2 is better than Comparative Example 1.

[0125] (2) Simulated sunlight test

[0126] The cosmetic compositions in the above-mentioned Examples 1-5 and Comparative Examples 1-2 and the control group samples (wrapped in tin foil, i.e., in a dark environment) were sampled with a test glass bottle of 20 grams, placed in a simulated fluorescent light box and under normal temperature and humidity conditions for 30 days, and the color changes on days 0, 5, 10, 15, 20, 25, and 30 were recorded respectively, and 1 g of samples were sampled at each time point for HPLC detection of the blue copper peptide content, and the blue copper peptide content on day 0 was used as a comparison to calculate the retention rate of the blue copper peptide in the composition (the calculation method is as described above, then n=7). Among them, the control group sample includes the following components in percentage by mass: 91.7% deionized water, 3% 1,3-propylene glycol, 4% 1,3-butylene glycol, 0.3% blue copper peptide, 0.5% 1,2-hexanediol, and 0.5% para-hydroxyacetophenone, i.e., it does not contain amino acid-based assemblies and anionic polysaccharide polymers).

[0127] The color change results and the blue copper peptide retention rate results are shown in Table 3 and Table 4, respectively.

[0128] Table 3. Color change results of simulated sunlight illumination test

[0129]

[0130]

[0131] The results of the 30-day simulated sunlight test of the cosmetic compositions in the above examples and comparative examples show that the cosmetic compositions in Examples 1-5 have good stability and no obvious abnormality. However, the color of Comparative Example 1 darkened on the 20th day, and the color of Comparative Example 2 darkened significantly on the 25th day. The simulated sunlight light stability of the cosmetic compositions in Examples 1-5 is significantly better than that of Comparative Examples 1-2.

[0132] Table 4. Retention rate of blue copper peptide in simulated sunlight test

[0133]

[0134] The results of the 30-day simulated sunlight test of the cosmetic compositions in the above examples and comparative examples show that the cosmetic compositions in Examples 1-5 have good stability and no obvious abnormalities. However, the color of Comparative Example 1 darkened on the 20th day, and the retention rate of blue copper peptide was 81.9%, and the color of Comparative Example 2 darkened significantly on the 25th day, and the retention rate of blue copper peptide was 78.3%. The simulated sunlight light stability of the cosmetic compositions in Examples 1-5 is significantly better than that of Comparative Examples 1-2.

[0135] (3) Intermittent sunlight test

[0136] 20 grams of the cosmetic composition in the above Examples 1-5 and Comparative Examples 1-2 were sampled in a test glass bottle and placed in an environment where direct sunlight could be irradiated for no less than 4 hours per day. The color changes on the 2nd, 4th, 6th, 8th, 10th, 12th and 14th days were recorded respectively. The test control group samples (whose components were the same as those of the control group samples in the simulated sunlight illumination test) were wrapped in tin foil as a blank control group. The results are shown in Table 5.

[0137] Table 5. Color change results of intermittent sunlight illumination test

[0138]

[0139] The compositions in the examples and comparative examples showed good stability in the 14-day intermittent sunlight illumination test without obvious abnormalities. However, the compositions in comparative examples 1 and 2 both faded on the 8th day and were dark blue on the 10th to 14th days. The intermittent sunlight illumination test of the compositions in examples 1-5 showed significantly better light stability than comparative examples 1-2.

[0140] (4) pH stability test

[0141] 20 grams of the cosmetic composition in the above Examples 1-5 and Comparative Examples 1-2 were sampled using a test glass bottle, the pH of the sample was tested, and the data was recorded. Under normal temperature and humidity and normal lighting conditions, the pH values ​​on the 1st, 15th, 30th, 45th, 60th, 75th, and 90th days were recorded to test the pH value change.

[0142] The results are shown in Table 6.

[0143] Table 6. pH stability test results

[0144]

[0145] In the 90-day pH stability test of the compositions in the above examples and comparative examples, the minimum pH difference before and after the test was 0.02 and the maximum pH difference was 0.05. Because the cosmetic composition in comparative example 1 does not contain an amino acid-based assembly, the pH difference before and after the test is 0.5, and the stability is significantly worse than that of other examples. The cosmetic composition in comparative example 2 does not contain anionic polysaccharide polymers, although the pH difference before and after the test is 0.05, its stability is significantly worse than that of examples 1-5.

[0146] The above results show that the cosmetic composition of Comparative Example 1 without an amino acid-based assembly has the worst result in the stability test, and the cosmetic composition of Comparative Example 2 contains an amino acid-based assembly. When the anionic polysaccharide polymer is replaced with hydroxyethyl cellulose, the result in the stability test is better than that of Comparative Example 1, but there is also a significant gap relative to Examples 1-5. This shows that the cosmetic composition provided by the present invention can effectively improve the photostability and heat stability of blue copper peptide.

[0147] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. Use of an amino acid-based assembly in the preparation of a reagent for improving the stability of blue copper peptide, wherein the amino acid-based assembly comprises arginine malate and / or glycyrrhizic acid arginine salt.

2. A reagent for improving the stability of blue copper peptide, characterized in that: The reagent for improving the stability of blue copper peptide comprises an amino acid-based assembly and an anionic polysaccharide polymer, wherein the amino acid-based assembly comprises arginine malate and / or glycyrrhizic acid arginine salt.

3. The reagent for improving the stability of blue copper peptide according to claim 2, characterized in that: The anionic polysaccharide polymer includes at least one of xanthan gum, sodium hyaluronate, gellan gum and sphingosine gum.

4. The reagent for improving the stability of blue copper peptide according to claim 2 or 3, characterized in that The reagents for improving the stability of blue copper peptide also include polyol, β-glucan, glycerol glucoside, preservative and antibacterial agent and deionized water; Alternatively, the reagent for improving the stability of blue copper peptide further comprises polyol, β-glucan, glycerol glucoside mixture, preservative and antibacterial agent and deionized water, and the glycerol glucoside mixture consists of glycerol glucoside, 1,2-pentanediol and water.

5. The reagent for improving the stability of blue copper peptide according to claim 4, characterized in that: The reagent for improving the stability of blue copper peptide includes the following components by mass: 0.1-30 parts of polyol, 0.01-0.5 parts of amino acid-based assembly, 0.01-2 parts of anionic polysaccharide polymer, 0.01-5 parts of β-glucan, 0.01-4 parts of glycerol glucoside, 0.1-10 parts of preservative and antibacterial agent, and 43.5-99.75 parts of water; Or, by weight, the reagent for improving the stability of blue copper peptide includes the following components: 0.1-30 parts of polyol, 0.01-0.5 parts of amino acid-based assembly, 0.01-2 parts of anionic polysaccharide polymer, 0.01-5 parts of β-glucan, 0.01-4 parts of glycerol glucoside mixture, 0.1-10 parts of preservative and antibacterial agent, and 43.5-99.75 parts of water; The glycerol glucoside mixture is composed of the following components in percentage by mass: Glyceryl glucoside 65%, 1,2-pentanediol 5% and water 30%.

6. The reagent for improving the stability of blue copper peptide according to claim 5, characterized in that: The polyol includes at least one of glycerol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, methyl propanediol and dipropylene glycol; The antiseptic and antibacterial agent includes at least one of 1,2-pentanediol, 1,2-hexanediol, p-hydroxyacetophenone, chlorphenesin, ethylhexylglycerin and methylparaben.

7. A cosmetic composition, characterized in that The cosmetic composition comprises the agent for improving the stability of blue copper peptide according to any one of claims 2 to 6 and blue copper peptide.

8. The cosmetic composition according to claim 7, characterized in that The cosmetic composition comprises the following components by weight percentage: Blue copper peptide 0.01%-5%, polyol 0.1%-30%, amino acid-based assembly 0.01%-0.5%, anionic polysaccharide polymer 0.01%-2%, β-glucan 0.01%-5%, glycerol glucoside 0.01%-4%, preservative and antibacterial agent 0.1%-10% and the balance to 100% water; Or, measured by mass percentage, the cosmetic composition comprises the following components: Blue copper peptide 0.01%-5%, polyol 0.1%-30%, amino acid-based assembly 0.01%-0.5%, anionic polysaccharide polymer 0.01%-2%, β-glucan 0.01%-5%, glycerol glucoside mixture 0.01%-4%, preservative and antibacterial agent 0.1%-10% and the balance to 100% water; The glycerol glucoside mixture is composed of the following components in percentage by mass: Glyceryl glucoside 65%, 1,2-pentanediol 5% and water 30%.

9. A method for preparing the cosmetic composition according to claim 8, characterized in that: Calculated by mass percentage, the process includes the following steps: Mix 0.01%-5% of blue copper peptide with 20% of water, then add 0.01%-0.5% of amino acid-based assembly, and mix to obtain a first mixed solution; 0.01%-2% of anionic polysaccharide polymer, 0.1%-30% of polyol and the balance of 100% of water are added into a vacuum emulsifying pot, heated to 80-85°C with stirring, kept warm in a water bath for 30 minutes, cooled to 70-75°C, 0.1%-10% of preservative and antibacterial agent is added, stirred and dissolved, and then cooled to 30-35°C, 0.01%-5% of β-glucan, glycerol glucoside mixture or 0.01%-4% of glycerol glucoside and the first mixed solution are added, and mixed to obtain the cosmetic composition.

10. Use of the cosmetic composition according to any one of claims 7 to 8 and / or the cosmetic composition prepared by the preparation method according to claim 9 in the preparation of repair and anti-aging skin care products.